Characteristics of Patients with Thoracolumbar Fractures at Dr. M. Djamil Padang Central General Hospital in 2018-2022 - Shafira, Zahra; Sahputra, Roni Eka; Noer, Mustafa; Rahmadian, Rizki; Burhan, Ida Rahmah; Irawati, Lili (Universitas Airlangga, 2025)
Background: Vertebral fracture is one of the traumas that results in the highest rates of disability and death. Vertebral fractures can occur in various regions, but more than 50% of cases occur in the thoracolumbar region T10-L2. This can be caused by several factors, such as age, gender, and BMI. More than 30% of patients have symptoms of chronic back pain accompanied by neurological deficits. This study discussed the characteristics of patients with thoracolumbar fractures at Dr. M. Djamil Padang Central General Hospital. Methods: This research is an observational descriptive study with a cross-sectional design. Research data were obtained from patient medical records, and the total inclusion sample is 139 patients with thoracolumbar fracture at Dr. M. Djamil Padang Central General Hospital in the 2018-2022 period. The data were processed and displayed as frequency distributions. Results: This research showed that the incidence of thoracolumbar fractures is found in 72 patients, with 72 being women. Mainly occurred between 15-64 years of age (73.4%), with 61.2% of cases caused by low energy trauma. As many as 62.6% of the patients received conservative management accompanied by surgery. Conclusion: This study concluded that thoracolumbar fractures often occur in women of reproductive age. The most common etiology is a fall from a height of less than three meters.